Patronage Project: The Performance of an Extensionist Project in Open Regime in Londrina County - Ferreira da Silva, Ana Lucia; Garcia Cavagnari, Alinne; Simitan Claro de Oliveira, Daniela; Luvison Nunes da Silva, Muriel; dos Santos Almeida, Nayara Aparecida (Guará Journal, 2019)
The present article aims presenting the actions developed through the Patronage Project - Londrina. The project is composed by a multidisciplinary team of graduated, recently graduated and advisors in their respective areas, which are: Law, Psycology, Administration, Social Service and Pedagogy in the State University of Londrina (PR), who act in a penal execution organ of open regime, denominated as Penitentiary Patronage of Londrina (PLDA). The unit is responsible for the fiscalization and attendance of graduates and beneficiaries with alternative sentences and penalties in semi-open regime, as much as the attendance and the pursuit so that the public is recognised as citizens with rights. Supported by a data collection of the own unit system; and by the life experience of the scholarshippers from the pedagogic area of this project, a quantitive and qualitative analysis is presented in relation to the work and actions developed since the year of 2014, when this extension project began, until 2018. From these data it will be presented the results obtained by the pedagogy section in this space of time in the district of Londrina.